Integration of Ushul Fiqh Principles in the Protection of Investor Assets in the Islamic Capital Market in Indonesia - Husni Rofiq; Usep Deden Suherman; Asep Ramdan Hidayat (CV. Sakura Digital Nusantara, 2026)
Purpose – This study aims to analyze the concept of investor asset protection in the Islamic capital market from the perspective of Ushul Fiqh principles, to identify relevant legal maxims as a normative foundation, and to examine their implementation in regulations, fatwas, and operational practices of the Islamic capital market in Indonesia. Design/methodology/approach – This research employs a descriptive qualitative approach through document analysis, interviews with fiqh experts, regulators, and practitioners, as well as non-participatory observation. Data analysis is conducted thematically through reduction, categorization, and interactive verification. Finding/Results – The findings indicate that investor asset protection is constructed through the integration of modern regulatory frameworks with Ushul Fiqh principles that emphasize justice, legal certainty, and risk mitigation. Five main pillars—clarity of contracts, justice, prevention of gharar (uncertainty) and maisir (gambling), risk mitigation, and the principle of trust (amanah)—form the foundation of investor protection. The legal maxims al-umūr bi maqāṣidiha (matters are judged by their objectives), al-yaqīn lā yazūlu bi al-shakk (certainty is not removed by doubt), al-ḍarar yuzāl (harm must be eliminated), and ḥifẓ al-amwāl (protection of wealth) function as a normative framework to establish a transparent, stable, and sustainable Islamic capital market Originality/Value – This study contributes by developing an Ushul Fiqh-based framework for investor asset protection in Indonesia's Islamic capital market, providing a new perspective for strengthening Sharia governance and improving investor confidence.